Draft Genome Sequence of the Pathogenic Oomycete Pythium insidiosum Strain Pi-S, Isolated from a Patient with Pythiosis - Rujirawat, Thidarat (Genome Announc, 2015)
Pythium insidiosum is an oomycete that causes a life-threatening infectious disease called pythiosis in humans and animals living in tropical and subtropical countries. Here, we report the first draft genome sequence of P. insidiosum. The genome of P. insidiosum is 53.2 Mb and contains 14,962 open reading frames.